Research on intelligent optimization of cryptogram service scheduling for service composition - Jian-jun LI; Bin YU; Wu-ping CHEN (Tongxin xuebao, 2013)
To improve the quality of cryptogram service, the cryptogram service architecture for service composition was proposed. And a hybrid discrete shuffled frog-leaping algorithm was proposed to solve cryptogram service scheduling problem. It uses the basic framework of the traditional frog-leaping algorithm and designs the encoding and decoding ac-cording. The corresponding individual vector updating method was re-designed. To improve search accuracy, the pro-posed algorithm was improved with six neighborhoods to optimize the best frog of the group and combined with variable neighborhood search algorithm. The proposed algorithm was tested on a set of standard instances and simulation experi-ments. The results show the effectiveness of the algorithms, and an optimal path to fulfill the users' request have been formed. It is suitable for the real life environment.